2003
DOI: 10.1128/iai.71.4.1733-1739.2003
|View full text |Cite
|
Sign up to set email alerts
|

Modification in the ppk Gene of Helicobacter pylori during Single and Multiple Experimental Murine Infections

Abstract: The bacterial pathogen Helicobacter pylori is highly adapted to the human stomach, and a high level of polymorphism is observed among clinical isolates. This polymorphism may be the consequence of adaptive changes during colonization, making a strain better able to survive, to evade the immune system, and to provoke a chronic infection. To investigate the mechanisms involved in the acquisition of diversity in H. pylori, mouse models of single infections, coinfections, and superinfections were developed. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…Many bacterial species contain another enzyme, PPK2, that also synthesizes poly P (18,51), but no ppk2 gene homolog was found in H. pylori genomes (51). In studies complementary to ours, others had reported that the ppk1 gene of Hp141v, a mutant H. pylori strain selected for an ability to maintain chronic infection in mice for 1 year, contained a 102-bp deletion, and that ppk1 inactivation reduced this strain's vigor in mice (7,8). They also suggested that inactivation of ppk1 in the unrelated strain X47-2AL made the strain unable to colonize mice.…”
supporting
confidence: 48%
“…Many bacterial species contain another enzyme, PPK2, that also synthesizes poly P (18,51), but no ppk2 gene homolog was found in H. pylori genomes (51). In studies complementary to ours, others had reported that the ppk1 gene of Hp141v, a mutant H. pylori strain selected for an ability to maintain chronic infection in mice for 1 year, contained a 102-bp deletion, and that ppk1 inactivation reduced this strain's vigor in mice (7,8). They also suggested that inactivation of ppk1 in the unrelated strain X47-2AL made the strain unable to colonize mice.…”
supporting
confidence: 48%
“…and P. aeruginosa, and for colonization of certain strains of H. pylori (7,49,63,70). Chickens are a natural zoonotic reservoir for C. jejuni, and contamination of commercial broiler flocks is thought to account for the majority of human C. jejuni infections (47).…”
Section: Figmentioning
confidence: 99%
“…In mammals, polyP seems to play a role in blood coagulation [6][7][8]. In bacteria, polyP has chaperone-like activity [9], and regulates stress response, ion channels [10,11] and infectivity as demonstrated for Pseudomonas aeruginosa [10,11,12] and Helicobacter pylori [13]. In trypanosomes, polyP metabolism has been recently characterized and as in pathogenic bacteria, trypanosomes with reduced polyP levels are significantly less virulent [14].…”
Section: Introductionmentioning
confidence: 98%